The influence of competence and transformational leadership style on the performance of village officials (study in villages in Sandai sub-district, Ketapang district) - Monika Olvi; Titik Rosnani (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of competence and transformational leadership style on the performance of village officials in Sandai District, Ketapang Regency. The study used a quantitative approach with a population of all village officials, while the sample was determined through a simple random sampling technique. Of the 99 targeted questionnaires, 88 questionnaires were declared eligible for analysis. The research data were analyzed using the Structural Equation Model–Partial Least Square (SEM-PLS) with the help of WarpPLS 8.0 software. The results showed that competence had a positive and significant effect on the performance of village officials. Meanwhile, transformational leadership style had a positive but insignificant effect on the performance of village officials. These empirical findings indicate that competence has a more dominant role in determining the performance of village officials than transformational leadership style. Therefore, efforts to improve the performance of village officials should be more focused on developing competence, either through training, skill improvement, or strengthening the capacity of village officials.